Investigation into the Fundamental Analysis of Stock Investment Instruments on the Indonesian Stock Exchange - Zulkifli Zulkifli (Enigma Institute, 2023)
Investors engage in thorough study and examination of various aspects that impact a company's performance and intrinsic value in order to make investment decisions. Fundamental analysis is scrutinizing a company's financial accounts, such as the balance sheet, income statement, and cash flow statement, in order to comprehend the company's financial well-being. Key elements examined in the fundamental analysis encompass revenue, net income, assets, debt, and operational cash flow. Financial ratio analysis, including metrics such as price-to-earnings (P/E), price-to-sales (P/S), price-to-book (P/B), and price-to-growth (PEG), is employed to evaluate if a company's stocks are reasonably priced or underestimated. Evaluating a stock's investment potential requires a thorough examination of a company's growth, future growth possibilities, and competition in the relevant sector and market. Assessing a company's success also requires considering its corporate governance and share ownership policies. Fundamental analysis enables investors to make well-informed investment decisions by thoroughly comprehending the firm, its financial performance, and the external factors that impact the organization. Fundamental analysis is a crucial tool for investors to evaluate the risk and potential return of an investment. It plays a significant role in establishing a successful stock investment plan.